Határvédelem megszervezése a visszatért Erdélyben : 1940-1944 - Suba, János (Közép-Európai Közlemények, 2015)
Based on the Second Viennese Decision the territories of Partium and North-Transylvania returned to the motherland. After the entry the guarding of the 1000-kilometer-long border started immediately. We can find different names for the military formations who took part in the protection of the border: border guard battalion, mountain battery of the border guard battalion, infantry battalion for border guarding, fort company of border guard battalion, border guards with mountain equipment, mountain guard battalion, Szekely border defense forces, border legion battalions, etc. In this study we survey the development and location of these formations with different names but the same task. We review the situation of the patrols rowed on the borders. The development of Transylvanian formations of the Army took place at the same time. In 1943 all the military for-mations got under the control of the Szekely border defense forces.